If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -2(4 + -1x) = 2 24 + (4 * -2 + -1x * -2) = 2 24 + (-8 + 2x) = 2 Combine like terms: 24 + -8 = 16 16 + 2x = 2 Solving 16 + 2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 2x = 2 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 2 + -16 2x = 2 + -16 Combine like terms: 2 + -16 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| 2+3x=32 | | 8x+6x+3y+2y=152.5+113 | | 9x-13x=-12 | | 4z+16=4(3z-2) | | 2m+1=5 | | 3(5y-2)=-21 | | 18=8.4 | | 4(2u+3)+4u+2=6(u-1)-4u | | f=p(1+rt) | | 8x^3+x^2-72x-9=0 | | 3x+7=2x+11 | | 70n-50n=80 | | 3(3u+2)+5u=6(u-4)-26 | | 8k-14=16 | | 7y-2=5y+8 | | 2(s-4)-7=19 | | 7+7c=6c-18 | | 18=-2(2x-7) | | 8x+2=9x+12 | | 2(5y-4)=32 | | 9y-6+y+8=42 | | 4.1+1.8n=0.14 | | 7x*4=12 | | 25+15x=100 | | 4x+5=7x | | 21+x=2x-36 | | A+(A+9)=99 | | 4b-10=6b | | 3n=m+1 | | 9c+1=-26 | | 4x-9=24 | | -9c+1= |